2019
DOI: 10.4102/curationis.v42i1.1906
|View full text |Cite
|
Sign up to set email alerts
|

Nurse graduates’ experiences and support needs: A qualitative systematic review of South Africa’s community service programme

Abstract: BackgroundThe student-to-nurse graduate transition is a pivotal phase in the professional development of nurses. In South Africa, this transition is part of a compulsory community service programme, which requires newly graduated nurses to work in rural and/or underserved areas for a period of 1 year.ObjectivesThe aim of this study was to review nurse graduates’ experiences and support needs during their transition in the compulsory community service programme.MethodsA qualitative systematic review of experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…In terms of implications for further nursing research, the findings reinforce the need to re-study the impacts of improved orientation programs intended for newly graduated nurses. There are numerous publications (Abiodun, Daniels, Pimmer, & Chipps, 2019;Ke, Kuo, & Hung, 2017;Lindfors, Meretoja, Kaunonen, & Paavilainen, 2018;Pasila, Elo, & Kääriäinen, 2017) that synthesize and clarify the needs of newly graduated nurses in terms of orientation programs and their benefits. Using these findings, it would be possible to develop an orientation program taking into account the specific learning needs of newly graduated nurses and then assess the impacts of this program on different parameters pertaining to humanistic caring.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of implications for further nursing research, the findings reinforce the need to re-study the impacts of improved orientation programs intended for newly graduated nurses. There are numerous publications (Abiodun, Daniels, Pimmer, & Chipps, 2019;Ke, Kuo, & Hung, 2017;Lindfors, Meretoja, Kaunonen, & Paavilainen, 2018;Pasila, Elo, & Kääriäinen, 2017) that synthesize and clarify the needs of newly graduated nurses in terms of orientation programs and their benefits. Using these findings, it would be possible to develop an orientation program taking into account the specific learning needs of newly graduated nurses and then assess the impacts of this program on different parameters pertaining to humanistic caring.…”
Section: Resultsmentioning
confidence: 99%
“…Brown and Crookes ( 2016 ) suggest that the newly graduated registered nurse is not ‘work ready’ and ‘does not feel ready’ and proper orientation programmes and development of the newly qualified registered nurse are essential. It would be important for institutions to ensure that autonomous practice and critical thinking are accompanied by the provision of adequate orientation and the availability of mentors and preceptors and can be supported through the use of information and communication technologies particularly in the rural areas (Abiodun et al 2019 ). It would also be important for institutions to ensure the provision of adequate orientation and the availability of mentors and preceptors, and these processes can be supported through the use of information and communication technologies to facilitate autonomous practice and critical thinking (Abiodun et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It would be important for institutions to ensure that autonomous practice and critical thinking are accompanied by the provision of adequate orientation and the availability of mentors and preceptors and can be supported through the use of information and communication technologies particularly in the rural areas (Abiodun et al 2019 ). It would also be important for institutions to ensure the provision of adequate orientation and the availability of mentors and preceptors, and these processes can be supported through the use of information and communication technologies to facilitate autonomous practice and critical thinking (Abiodun et al 2019 ). This is further corroborated by Makua ( 2016 ) who found that there is lack of professional development and support for community service nurses in most public institutions and that this may contribute to the lack of competency of these nurses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations